Study of Actinobacteria and their Secondary Metabolites from Various Habitats in Indonesia and Deep-Sea of the North Atlantic Ocean - Risdian, Chandra (2020)
Actinobacteria are Gram-positive bacteria and the prolific producers of bioactive molecules. In the course of drug discovery from actinobacterial sources, some samples were taken from different locations and habitats of Indonesia and isolation of Actinobacteria was conducted thereof. Totally 196 strains of Actinobacteria were isolated, and approximately half of them were characterized by 16S rRNA gene analysis. Around two-thirds of them were detected as Streptomyces. One of the Streptomyces strains, i.e., strain SHP 1-2 produced active extracts against some microbial pathogens. Analysis and isolation of compounds from its extract revealed that two novel molecules, which are indolactam derivatives, were found from it. Polyphasic taxonomy study of strain SHP 1-2 suggested that this strain is a novel species in the Streptomyces group. Another study from different strains suggested that strain MAE-11, isolated from mangrove area, was identified close to Kitasatopora and Streptomyces species and generated active extract against hepatitis C virus (HCV). The extract was known to contain bafilomycin D as the molecule that was responsible for the antiviral activity. Isolate 196526CR was detected as Amycolatopsis species and could produce an extract that showed activity against some tested microbes. The compound analysis and isolation from its extract indicated that nitrosoxacin C possesses property as an antimicrobial compound. Chemotaxonomy study of strain ASO4wet, which was previously isolated from deep-sea in the North Atlantic Ocean, was also conducted and the data supported that ASO4wet belongs to the genus Streptomyces. The strain is described as the novel species. Actinobakterien sind Gram-positive Bakterien und die ergiebigsten Produzenten bioaktiver Moleküle. Im Zuge der Wirkstoffforschung aus Actinobakterien wurden einige Proben an verschiedenen Orten und Lebensräumen Indonesiens entnommen und daraus Actinobakterien isoliert. Insgesamt wurden 196 Aktinobakterien-Stämme isoliert und etwa die Hälfte von ihnen ...